INDUCTIVE-DEDUCTIVE LEARNING APPROACH TO DEVELOP STUDENTS’ MATHEMATICAL PROBLEM SOLVING SKILLS AND SELF EFFICACY - Teguh Imam Agus Hidayat; Jozua Sabandar; Mumun Syaban ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study was a pretest-posttest designed control group experiment, aimed at reviewing the role of inductive-deductive approach on Islamic Junior High School students’ skills in mathematical problem solving and self efficacy. This research involved 56 grade eight students, a set of problem solving ability tests and a set of self efficacy scale. The result found that in the extent of mathematical problem solving skills and self efficacy, students who received problem solving-based learning achieved better quality than students who received conventional learning, either overall or based on the early mathematical ability (EMA). The interaction between learning and EMA in achieving and increasing problem solving skill showed no significant difference. Other than that, we found robust association between mathematical problem solving skills and self efficacy.